2023
DOI: 10.3390/cells12131782
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeleton Polymerization and Focal Adhesion as Important Factors in the Pathomechanism and Potential Targets of Mucopolysaccharidosis Treatment

Abstract: The main approach used in the current therapy of mucopolysaccharidosis (MPS) is to reduce the levels of glycosaminoglycans (GAGs) in cells, the deposits considered to be the main cause of the disease. Previous studies have revealed significant differences in the expression of genes encoding proteins involved in many processes, like those related to actin filaments, in MPS cells. Since the regulation of actin filaments is essential for the intracellular transport of specific molecules, the process which may aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…We next performed function enrichment analysis on these DEPs (Figure C,D) and found that a majority of them are associated with controlling the transport of molecules inside and outside the cell, signaling pathways, and regulation of cellular morphology. Based on the current reports on the pathogenesis of MPS I and the accuracy and credibility of the obtained enrichment data, 20 relevant proteins (Table S2) were selected from cellular components involved in endocytic vesicle, growth factor binding, and vesicle lumen for PRM verification. Serum samples from another 6 MPS I and 6 healthy controls were collected for PRM experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next performed function enrichment analysis on these DEPs (Figure C,D) and found that a majority of them are associated with controlling the transport of molecules inside and outside the cell, signaling pathways, and regulation of cellular morphology. Based on the current reports on the pathogenesis of MPS I and the accuracy and credibility of the obtained enrichment data, 20 relevant proteins (Table S2) were selected from cellular components involved in endocytic vesicle, growth factor binding, and vesicle lumen for PRM verification. Serum samples from another 6 MPS I and 6 healthy controls were collected for PRM experiments.…”
Section: Resultsmentioning
confidence: 99%
“…9 The study found that the diagnosis time of MPS I in various regions is generally delayed. 10 It is necessary to facilitate the detection of biochemical markers, but the complex pathogenesis limits the application of the commonly used urine glycosaminoglycan assay. 11 Most studies have simply focused on biomarkers of certain body fluids or other kinds of biospecimens in MPS I patients, which may result in a large research bias for the reason that MPS I is rare and the number of included patients is usually not enough.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, apart from secondary biochemical changes and dysmorphology in cellular organelles [ 13 , 14 ], crucial processes occurring in MPS cells were demonstrated to be significantly affected [ 15 ]. They include proteasome activity [ 16 ], ion homeostasis [ 17 ], signal transduction [ 18 ], cell cycle [ 19 ], vesicle trafficking [ 20 ], actin cytoskeleton polymerization [ 21 ], and apoptosis [ 22 ]. Dysregulation of the last of the mentioned processes has been demonstrated mostly by finding changes in the expression of the genes involved, directly or indirectly, in apoptosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used fibroblasts derived from MPS IVA and IVB patients as cellular models of the diseases. Such cells were previously employed during MPS investigations, indicating that experiments with fibroblasts can give reliable results in studies on molecular mechanisms of MPS [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%